Variable stoichiometry of the TatA component of the twin-arginine protein transport system observed by in vivo single-molecule imaging. - Leake, M; Greene, N; Godun, R; Granjon, T; Buchanan, G; Chen, S; Berry, R; Palmer, T; Berks, B (2008)
The twin-arginine translocation (Tat) system transports folded proteins across the bacterial cytoplasmic membrane and the thylakoid membrane of plant chloroplasts. The essential components of the Tat pathway are the membrane proteins TatA, TatB, and TatC. TatA is thought to form the protein translocating element of the Tat system. Current models for Tat transport make predictions about the oligomeric state of TatA and whether, and how, this state changes during the transport cycle. We determined the oligomeric state of TatA directly at native levels of expression in living cells by photophysical analysis of individual yellow fluorescent protein-labeled TatA complexes. TatA forms complexes exhibiting a broad range of stoichiometries with an average of approximately 25 TatA subunits per complex. Fourier analysis of the stoichiometry distribution suggests the complexes are assembled from tetramer units. Modeling the diffusion behavior of the complexes suggests that TatA protomers associate as a ring and not a bundle. Each cell contains approximately 15 mobile TatA complexes and a pool of approximately 100 TatA molecules in a more disperse state in the membrane. Dissipation of the protonmotive force that drives Tat transport has no affect on TatA complex stoichiometry. TatA complexes do not form in cells lacking TatBC, suggesting that TatBC controls the oligomeric state of TatA. Our data support the TatA polymerization model for the mechanism of Tat transport.